Content Creator Legal Ability For Submit Banking Credit Agreement in Indonesia - Sandy Victor Hukunala (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2021)
Introduction: Advances in information technology and digitization bringing up a new job profession called Content Creator. To support the quality of their work, content creators need equipment. The need for this equipment is often become content creator challenge. One way that can be done is to apply for credit to the bank. The problem arises when the profession of a content creator has not been considered